A case study of health information system workflow on mitigating opioid drug abuse in Saudi Arabia's healthcare system / Alogaili Fahad Abdulrahman - Alogaili, Fahad Abdulrahman (2021)
The hospitals in Saudi Arabia, which have been studied in this research, are almost entirely automated. Healthcare information systems (HIS) are quite efficient; however, the health information exchange (HIE) is absent in the existing systems for different hospitals. Opioid drugs are an addictive substance, Saudi Arabia has the highest mean of drug abuse disorders in the region (680.5, group mean was 401.8). The lack of HIE had contributed significantly to the increase of opioid drug abuse in Saudi Arabia. If a patient has taken opioid as a painkiller, an interoperable system must have the information available for the healthcare department all over Saudi Arabia. Currently, this is not happening, and the HIE is limited. Authorization by the patient is one of the biggest challenges in HIE, as authorization is important to exchange health data through various technology and healthcare platforms. It may also lead to legal risks if the health information of the patient is shared without the patient's authorization. In response to the growing requirement of interoperability in healthcare system, this research aims to propose an interoperable and integrated HIS workflow processes that capable in mitigating abuse issues in Saudi Arabia. This study explored the magnitude of the opioid abuse issues in Saudi Arabia within the context of improper HIS design to identify abuse patients. Objectives associated with this research have been achieved using a qualitative approach with a case study research design. First stage was the observation conducted on sites to understand the practice of HIS workflow and how participants are using the currents HIS model. The primary data was collected through questionnaires that were filled out by the pharmacists and physicians. Interviews were also conducted with the physicians and pharmacists. Some secondary data has also been used in developing responses to the research questions. This research has also identified the current workflow processes of prescribing opioid drugs using HIS in Saudi Arabia while exploring physician and pharmacist perception on the usage of current HIS model regarding opioid drug abuse. Primary data collected from the physicians and pharmacists involved in the field has shown that they are aware of the existing situation that prevails in Saudi Arabia regarding the abuse of opioids. The suggested system workflow processes provide coordination of various sections of the healthcare industry in a manner that makes tracing opioid abuse possible. E-prescription is vital tool in this regard. Interoperability is the key to resolving this issue. At the end of this research, validation of the improved HIS workflow process is done by exploring participants’ and experts’ impressions on the proposed interoperable HIS workflow processes. For this purpose, information was collected from the participants, field experts, and IT professionals. The participants and healthcare experts have reviewed the proposed system and considered as valid for hospitals in Saudi Arabia. The IT experts also believe that such an interoperable system can work very well in Saudi Arabian hospitals. This study is a steppingstone for future research, which can help in overcoming drug abuse and misuse issue in Saudi Arabia. The same proposed HIS workflow processes can be applied in other countries to help control the drug abuse issues all over the world.